(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
Humanity is forced to exist in conditions of increasing social instability today, deepening economic crisis, changing the conditions of existence of the individual in the society, forming new parameters of socialization of the individual. Against the background of local urushlar and "colorful" revolutions, migration flows are sharply decreasing. In such circumstances, the issue of tolerance really has an international nature. His decision on the prospect of helping to open the nodes of a multi-issue "hot" and "frozen" dispute. Dependence-achieving mutual reconciliation in the dialogue of opposing parties is impossible without a certain degree of mutual tolerance, acceptance of cultural differences, denial of monopoly in the possession of absolute truth